PENGARUH PROFITABILITAS, LEVERAGE, CAPITAL INTENSITY, SALES GROWTH DAN UKURAN PERUSAHAAN TERHADAP PENGHINDARAN PAJAK - Sasongko Wahyu Widodo; Sartika Wulandari (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2021)
This research aimed to investigate the effect of profitability, leverage, capitalintensity, sales growth, and firm size against tax avoidance. Measurement of taxavoidance in this research used effective tax rate (ETR). This research usedmanufacturing companies listed in Indonesia Stock Exchange in 2017-2019. Thesample selection method used purposive sampling technique and obtained 140sample. The data analysis used was multiple linear regression test. The result ofthe analysis showed that profitability and firm size has no effect on tax avoidance.Meanwhile leverage and capital intensity has significant positive effect on taxavoidance. The result of the test showed that sales growth has a significantnegative effect on tax avoidance.